Formulasi dan Uji Efektivitas Sediaan Gel Ekstrak Buah Bit (Beta vulgaris L) Terhadap Penyembuhan Luka Tikus Model Diabetes Yang Diinduksi Aloksan - Kinanti Maharani; Astriani Natalia Br. Ginting; Roy Indrianto Banggar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Diabetic ulcers are serious complications of diabetes mellitus that are difficult to heal due to hyperglycemia, oxidative stress, and infection. Beetroot (Beta vulgaris L.) contains betalains, flavonoids, and polyphenols which possess antioxidant and anti-inflammatory activities to accelerate tissue regeneration. Objective: This study aims to formulate beetroot ethanol extract into a gel preparation and test its effectiveness on wound healing in alloxan-induced diabetic rat models. Methods: This experimental study included beetroot extraction using 96% ethanol maceration, phytochemical screening, and gel formulation with varying extract concentrations (5%, 10%, and 15%). Thirty male rats were induced with alloxan (150 mg/kgBW) to reach a diabetic state, then given a 2 cm incisional wound. Rats were divided into 6 groups: Normal, Negative Control (gel base), Positive Control (Chloramphenicol), and extract gel groups of 5% (F1), 10% (F2), and 15% (F3). Wound length was observed for 14 days. Results: Phytochemical screening showed the extract was positive for alkaloids, flavonoids, saponins, steroids, and tannins. Physical evaluation of the preparation (pH, homogeneity, viscosity, and spreadability) met SNI standards. The effectiveness test results showed significant differences (p < 0.05) between treatment groups. The F3 group (15%) showed the best healing rate, comparable to the positive control and normal groups, with an average wound length of 0 mm by day 14. Conclusion: Beetroot ethanol extract gel has good physical stability, and the 15% concentration is the most effective in accelerating wound healing in diabetic rat models.